Obtaining Composite Zr-Al-O Coating on the Surface of Zirconium by Microplasma Oxidation; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Gubaydulina T. A. Tatiana Anatolievna; Kuzmin O. S. Oleg Stanislavovich; Sergeev V. P. Viktor Petrovich; Fedorishcheva M. V. Marina Vladimirovna; Kalashnikov M. P. Mark Petrovich (2014, 2014)
Title screen